Response of long melon (Cucumis melo var utilissimus) to foliar application of plant-growth substances - ARORA, S K; PANDITA, M L; PRATAP, P S; BATRA, B R (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during summer season of 1991 and 1992 to study the effect of foliar sprays of ethephon, gibberellic acid (GA3), maleic hydrazide (MH) and naphthalene acetic acid (NAA) on vegetative growth. flowering and yield of 'Hisar Local Selection' long melon (Cucumis melo L. var utilissimus Duth. & Full.). GA3 @ 25 mg/litre applied atthe stage of 2 and 4 true leaves improved the main vine length (3.97 m), whereas MH @ 200 mg/litre suppressed it to minimum (2.11 m). NAA @25 mg/litre, ethephon at all the concentrations and MH @50 and 100 mg/litre also suppressed the main vine length compared with the untreated control. Ethephon @ 250 mg/litre, which effectively increased thebranches/plant (10.S) compared witlt the control (5.2), reduced the internodal length (8 cm) and male: female ratio (3.1), and gave the earliest (68 days) and the maximum number of female flowers (27), fruits (17.7) and total yield (1.36 kg/plant). Enthephon @ 250 mg/litre gave the maximum fruit yield (29.76 tonnes/ha.) and GA3 @ 25 mg/litre the minimum (11.08 tonnes/ha).